Phân rã Gamma nối tần của hạt nhân 59Ni - Nguyễn, An Sơn (Trường Đại học Đà Lạt, 2012)
The experiments of nuclear structure research have been doing in Nuclear Research Institue (NRI), it is based on technique of summation of coincidence pulses and nuclear reactions with thermal neutron from reactor. In this report, the rearch results of gamma cascad decay of 59Ni.